1963
DOI: 10.1111/j.1748-1716.1963.tb02734.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Histochemical Evaluation of the Distribution of Catecholamines in the Rabbit and Guinea Pig Hearts

Abstract: A A~~~~~4~~~, E. T., K. FUXE and hf. L. TORCHIANA, Chemical and histochemical evaluation o f the distribution o f catecholamines in the rabbit and guinea pig hearts. Acta physiol. scand. 1963. 59. 184-192. -Chemical determinations of noradrenaline (NA), adrenaline (.4), and dopamine (DA) were made in the right and left atria and ventricles (RA, LA RV. LV) of rabbit and guinea pig hearts. The concentration of these amines was also studied in the sino-auricular (SA) node of the rabbit. Some of these tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1966
1966
1979
1979

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(41 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…Secondly the effect of noradrenaline in producing a greater inotropic effect for the same chronotropic effect than isoprenaline, before but not after cocaine, may be explained by the more rapid removal of noradrenaline by the uptake processes and thus a greater reduction in concentration at the site of action in the sinu-atrial node than in the muscle of the left ventricle. Angelakos, Fuxe & Torchiana (1963) have shown that the sinu-atrial nodes of the guinea-pig and rabbit hearts have a higher concentration of noradrenaline than the left ventricle and using a fluorescence histochemical technique have associated the higher concentration of noradrenaline in the sinu-atrial node with a denser adrenergic innervation. If it is assumed that the noradrenaline concentration in cardiac tissue reflects the density of adrenergic innervation, then the sinu-atrial node of the dog also possesses a denser adrenergic innervation than the left ventricle (Angelakos, 1965).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly the effect of noradrenaline in producing a greater inotropic effect for the same chronotropic effect than isoprenaline, before but not after cocaine, may be explained by the more rapid removal of noradrenaline by the uptake processes and thus a greater reduction in concentration at the site of action in the sinu-atrial node than in the muscle of the left ventricle. Angelakos, Fuxe & Torchiana (1963) have shown that the sinu-atrial nodes of the guinea-pig and rabbit hearts have a higher concentration of noradrenaline than the left ventricle and using a fluorescence histochemical technique have associated the higher concentration of noradrenaline in the sinu-atrial node with a denser adrenergic innervation. If it is assumed that the noradrenaline concentration in cardiac tissue reflects the density of adrenergic innervation, then the sinu-atrial node of the dog also possesses a denser adrenergic innervation than the left ventricle (Angelakos, 1965).…”
Section: Resultsmentioning
confidence: 99%
“…This may be an alternative explanation for the preferential potentiation of the tension responses to isoprenaline by reserpine. If there were a greater receptor density in the right atrium than in the left atrium, which is possible in view of its denser innervation (Angelakos, Fuxe & Torchiana, 1963), then with each dose of isoprenaline a greater proportion might be occupied in the left atrium. Thus there are fewer spare receptors (Stephenson, 1956) and receptor proliferation might be expected to have a more marked effect upon the response size than in the right atrium where there may be more spare receptors and an increase in total receptor population would have proportionately less effect.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference from the chronotropic responses is not clear. It could reflect a different spatial relationship of the terminal axons with conducting tissue on the one hand and with myocardial fibres on the other, or it might be related to the evidence (Angelakos, Fuxe & Torchiana, 1963) that sinoatrial tissue is associated with a far denser adrenergic nervous plexus than is atrial muscle.…”
Section: Effect Of Blood Oestrogen On Uptake2mentioning
confidence: 99%